Bicultural landscapes and ecological restoration in the compact city: The case of Zealandia as a sustainable ecosanctuary. Issue 1 (2nd January 2019) - Marques, Bruno; McIntosh, Jacqueline; Hatton, William; Shanahan, Danielle
Abstract : In the context of the highly compact bicultural capital city of Wellington, New Zealand, this paper explores the development of an ecosanctuary initiated by the community. The indigenous flora and fauna was damaged as a result of the introduction of mammalian predators and aggressive plant species when the country was colonized, and through intensive urbanization. The restoration of the indigenous flora and fauna and the reintroduction of birdsong has resulted in a significant increase in commercial ecotourism. This paper explores health and well-being opportunities resulting from seeing the sanctuary through a Māori lens. It examines the phenomenon of Zealandia, where green and blue infrastructures foster emerging ecologies while accommodating visitor services and improving the social, cultural, economic, and environmental health of the city. It finds that the benefits of this compact urban landscape far exceed the original goals of the project and it offers new prospects for health and well-being through intensification by addressing sustainability holistically and including socio-cultural perspectives and initiatives.